Pemasaran Digital, Pembayaran Digital, dan Kinerja UMKM Pangan: Peran Mediasi Keunggulan Kompetitif - Indrajit Wicaksana; Yuridistya Primadhita; Syifa Fauziah (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2026)
This study presents an analysis of the influence of digital marketing and digital payment on competitive advantage and food SME performance, as well as examines the mediating role of competitive advantage on food SME performance. The study involved 60 food SME actors in East Bogor selected using a purposive sampling technique. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results of the study indicate that the competitive advantage and performance of food MSMEs are influenced by digital marketing, but not by digital payment. Competitive advantage also affects the performance of food MSMEs. In addition, competitive advantage is proven to mediate the effect of digital marketing on food SME performance, but it does not mediate the effect of digital payment. These findings indicate that the implementation of digital marketing has become an important strategy for improving the competitiveness and performance of food SMEs in the cashless economy era, particularly in East.